Challenges faced by entrepreneurs and the performance of small and medium scale (SMEs) In Nigeria: An Intellectual capital issue - Tobora, Omolomo Odunayo (SciPress Ltd, 2015)
An entrepreneur is one who contributes significantly more than others to the economy by virtue of innovation and realizing new combinations. Which involve creation of a new product, a new method of production, the opening of a new market, the capture of a new source of supply, or a new organization of industry. Entrepreneurship of SMEs performance in knowledge -based economy. In addition, this study also explores the challenges which are facing small and medium enterprises (SMEs) in Nigeria. The significance of the study will add to the knowledge about current issues relating to SMEs in Nigeria The main thrust of this study is challenging which face Entrepreneur of small and medium scale enterprises (SMEs) on business performance in Nigeria.